Notes on the genus Coelocraera from Cameroon with the description of four new species (Coleoptera: Histeridae: Exosternini) - Vienna, Pierpaolo; Simon-Pražák, Jan; Baňař, Petr (Zootaxa, 2025)
Four new species of Coelocraera (Histeridae: Histerinae: Exosternini) are described from Cameroon: Coelocraera lucida sp. nov., C. parumstriata sp. nov., C. punctatifrons sp. nov. and C. tishechkini sp. nov. New Cameroon country records of five species are reported. A list of Coelocraera species of Cameroon is provided and accompanied by photos of all reported species.